Analisis Perkembangan Dan Dampak Ekonomi Digital Pada Usaha Mikro Kecil dan Menengah (UMKM) Di Kabupaten Lombok Timur - Nur Fitri Eka Asbarini; Hengky Setiawan; Putri Surya Safara; Sultanil Jamil (LPPM STAI DARUSSALAM LAMPUNG, 2024)
The digital economy has brought significant changes to various societal economic activities, shifting previously manual processes to digital-based systems. This study aims to analyze the impact of digital economic development on Micro, Small, and Medium Enterprises (MSMEs) in East Lombok Regency, particularly in terms of business income improvement. The research employs a descriptive qualitative method, utilizing primary data collected through interviews and observations of 100 MSMEs, and secondary data from literature, statistics, and official documents. The findings reveal that digitalization facilitates MSMEs in expanding their market reach from local to national and international levels. MSMEs in East Lombok Regency utilize social media and e-commerce platforms, such as Shopee and Tokopedia, to market their products, increasing brand visibility and sales volume. Digitalization also enhances operational efficiency and creates opportunities for faster business growth compared to traditional methods.